Balance and injury in elite Australian footballers - Hrysomallis, C.; McLaughlin, P.; Goodman, C. (International Journal of Sports Medicine, 2007)
This project measured pre-season balance ability and determined its relationship to knee and ankle ligament injuries during the season for professional Australian footballers. The balance test involved the players stepping onto a foam balance mat on top of a force plate and maintaining single limb balance. Throughout the playing season, injuries were monitored. The results from two hundred and ten players participating in this project were analysed. During the 2003 season, 8 % (17 out of 210) sustained a knee ligament injury and 10 % (21 out of 210) sustained an ankle ligament injury. Multivariate analysis revealed that pre-season balance ability was a significant independent predictor of ankle ligament injury. Players with low balance ability had at least twice as many ankle ligaments injuries as those with average or good balance ability. Balance ability was not a significant predictor of knee ligament injuries. The height of the players was the only significant independent predictor of knee ligament injuries. Low pre-season balance ability was associated with an increased risk of ankle ligament injury. A modifiable injury risk factor has been identified. Research is now required to determine the optimal training regime to enhance balance ability and whether this translates to a reduction in the incidence of ankle injuries.